Designing Marketing Mix Improvement Programs Based On Purchasing Decision Influence Of Polar Products - Alifan Nurfatwa Mahasidhqi; Budi Praptono; Ima Normalia Kusmayanti (eProceedings of Engineering, 2020)
Abstract Currently there are many fashion brands in Indonesia that market their products online and offline, usually brands in Indonesia have their own â€œdistroâ€ as their offline stores. Many product marketing is done online one of them through the Instagram platform. Currently, Polar only used Instagram to market its products. Therefore, Polar needs to have variety of marketing programs ti incrase sales. This study is aimed to identify factors influencing purchasing decisions of Polarâ€™s customers and design marketing mix programs based on the purchasing decisions. To achieve the research objectives, researchers used a mix marketing and multiple regression methods. Based on these findings, weighting on the seven marketing mix programs was conducted. The results are research and analysis conducted, the conclusion is correlation test results (R) and determination (R2) prove that Consumer Behavior (X1) and Product Quality (X2) have a positive and very strong influence on Purchasing Decisions (Y) while Product Prices (X3) have a negative influence but has a strong influence on Purchasing Decisions (Y). Keywords â€“ Product purchasing decisions, mix marketing, multiple regression methods.